The Reality of Education in Japan from 1912 to 1926: A Historical Study - Aziz , Dr. Vian Hassan (Thi Qar Arts Journal, 2024)
Education is of great importance in building nations and is a fundamental element in their development and renaissance. We cannot look at the Japanese renaissance without clearly seeing the subject of education. The modern Japanese education system underwent extensive reforms that began in the late 19th century and then flourished at the beginning of the 20th century. Education in Japan during the period (1912-1926) was of great importance in the general state policy at all levels, from kindergartens to university stages. Education had the largest share in that policy, and perhaps the standard of ethics contributed to the development of education in Japan, making it advance by leaps and bounds in a relatively short period. In this research, we addressed the reality of education in Japan during the period 1912-1926, focusing on the government’s educational policy and the reality and development of educational institutions during that period, relying on several diverse and relevant sources.